Handbook on benefits and privileges of U.P. Faculty and Staff. - Azanza, Patrick Alain (Diliman, Quezon City Human Resources Development Office, 1995)
Informs employees of the University of the Philippines about all the benefits and privileges that they can have as U.P. employees. It states the details of the benefits and privileges and the responsibilities of the employees with regards to these benefits and privileges.
Produced by the Human Resources Development Office UP Diliman (1993) ; Reprint (1995)